Population Genomics Reveals Shallow Genetic Structure in a Connected and Ecologically Important Fish From the Northwestern Pacific Ocean - Zhang, Bai-Dong; Li, Yu-Long; Xue, Dong-Xiu; Liu, Jin-Xian (Frontiers in Marine Science, 2020)
Genetic variation at the genomic level is invaluable to identify ﬁsh stock structure in fisheries management. It has been widely accepted that populations of marine fishes are highly connected owing to fewer barriers to gene flow and increased connectivity resulting from greater dispersal abilities. Since population genomic approaches have increased the accessibility and resolution of population genetic data, it further facilitates to study and detect previously unidentified structures as well as signatures for natural selection in wild populations. In the present study, restriction-site associated DNA (RAD) sequencing was applied to the samples of genome-wide single nucleotide polymorphisms (SNPs) of Engraulis japonicus, a small pelagic fish of ecological and economic importance in the northwestern Pacific. To assess population genetic structure as well as detection for local adaptation of E. japonicus, a total of 389 individuals from six regional populations of the northwestern Pacific were collected and a set of 12,627 SNPs was developed. Marginal significant genetic structure (average FST value was approximately equal to 0.002) was detected between regional populations of “the Bohai Sea population (BHS)” and the “the Japan Sea population (JPS)” as well as between “the North Yellow Sea population (NYS)” and the “the Japan Sea population (JPS)”. Moreover, no sign of local adaptation was detected, which might be the product of high gene flow among regional populations. Overall, our results improve the understanding of fine-scale population genetic structure in E. japonicus and potentially identify management unit in this species area.